Properties of oil palm shell lightweight concrete with ceramic tile powder as a partial cement replacement - Tanash, Alaa Omar; Khairunisa, Muthusamy; Mohd Faizal, Md Jaafar; Sofia Adibah, Jasni; Hilal, Nahla N. (Semarak Ilmu Publishing, 2025)
Globally, the concrete production continues to expand with rapid urbanization. Environmental pollution caused by release of greenhouse gases of cement factory, disposal of ceramic tile waste from construction project and dumping of oil palm shell of palm oil mills need to be resolved. Therefore, a new ecologically friendly concrete materials formed using industrial wastes as mixing ingredient should be used. The current study investigates the influence of ceramic tile powder as a partial substitution for cement on the workability and hardened properties of oil palm shell concrete. A total of six mixtures were tested, each containing different percentage of ceramic tile powder in relation to the weight of the cement: 0%, 10%, 20%, 30%, 40% and 50%. All samples were water cured up to 28 days before testing. The mixtures were tested to determine the workability, dry density, compressive strength, splitting tensile strength and water absorption. Blending of 10% ceramic tile powder improves the compressive strength of oil palm shell concrete owing to pozzolanic reaction effect. Integration of ceramic tile powder up to 50% produce concrete with water absorption lower than 10% indicating its good quality. Success in blending ceramic tile powder in oil palm shell concrete production would reduce waste accumulation at wasteyard and lower cement consumption for greener environment.